APOE interacts with tau PET to influence memory independently of amyloid PET in older adults without dementia. Issue 1 (4th September 2020) - Weigand, Alexandra J.; Thomas, Kelsey R.; Bangen, Katherine J.; Eglit, Graham M.L.; Delano‐Wood, Lisa; Gilbert, Paul E.; Brickman, Adam M.; Bondi, Mark W.
Abstract: Introduction: Apolipoprotein E (APOE) interacts with Alzheimer's disease pathology to promote disease progression. We investigated the moderating effect of APOE on independent associations of amyloid and tau positron emission tomography (PET) with cognition. Methods: For 297 nondemented older adults from the Alzheimer's Disease Neuroimaging Initiative, regression equations modeled associations between cognition and (1) cortical amyloid beta (Aβ) PET levels adjusting for tau and (2) medial temporal lobe (MTL) tau PET levels adjusting for Aβ, including interactions with APOE ε4‐carrier status. Results: Adjusting for tau PET, Aβ was not associated with cognition and did not interact with APOE. In contrast, adjusting for Aβ PET, MTL tau was associated with all cognitive domains. Further, there was a stronger moderating effect of APOE on MTL tau and memory associations in ε4‐carriers, even among Aβ‐negative individuals. Discussion: Findings suggest that APOE may interact with tau independently of Aβ and that elevated MTL tau confers negative cognitive consequences in Aβ‐negative ε4 carriers.